Music on the Move - Fosler-Lussier, Danielle (Open textbook library., 2020)
Music is a mobile art. When people move to faraway places, whether by choice or by force, they bring their music along. Music creates a meaningful point of contact for individuals and for groups; it can encourage curiosity and foster understanding; and it can preserve a sense of identity and comfort in an unfamiliar or hostile environment. As music crosses cultural, linguistic, and political boundaries, it continually changes. While human mobility and mediation have always shaped music-making, our current era of digital connectedness introduces new creative opportunities and inspiration even as it extends concerns about issues such as copyright infringement and cultural appropriation. With its innovative multimodal approach, Music on the Move invites readers to listen and engage with many different types of music as they read. The text introduces a variety of concepts related to music's travels—with or without its makers—including colonialism, migration, diaspora, mediation, propaganda, copyright, and hybridity. The case studies represent a variety of musical genres and styles, Western and non-Western, concert music, traditional music, and popular music. Highly accessible, jargon-free, and media-rich, Music on the Move is suitable for students as well as general-interest readers. Citable link: https://doi.org/10.3998/mpub.9853855